2017
DOI: 10.1016/j.cocis.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Surface forces in unconventional oil processing

Abstract: As the world population and energy demand grow every year, unconventional oil plays an increasingly more important role in satisfying our energy needs. At 3.2 trillion barrels of currently recoverable unconventional oil, and with in-place reserves putting Canadian oil sands alone at 1.7 trillion barrels, it is becoming increasingly important to find both economical and environmentally sound technologies to bring this resource to market. Characterized by its high density and high viscosity, many extraction meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…When an external force is applied, the water film close to the surface can be easily removed or ruptured, providing favourable conditions for its attachment to air bubbles or bitumen. Recent research clearly demonstrated that increasing solid surface hydrophobicity led to a lower film drainage resistance, and faster liquid flow …”
Section: Hydrophobicity Of Bitumen Bubbles and Solidsmentioning
confidence: 99%
See 1 more Smart Citation
“…When an external force is applied, the water film close to the surface can be easily removed or ruptured, providing favourable conditions for its attachment to air bubbles or bitumen. Recent research clearly demonstrated that increasing solid surface hydrophobicity led to a lower film drainage resistance, and faster liquid flow …”
Section: Hydrophobicity Of Bitumen Bubbles and Solidsmentioning
confidence: 99%
“…It therefore becomes apparent that water‐based bitumen extraction from oil sands is a unique mineral flotation system, involving interactions between solids, oil droplets (bitumen), and air bubbles. The surface forces involved in processing oil sands have recently been critically reviewed, which has provided insights into the molecular interactions occurring in bitumen recovery from water‐based oil sand extraction. A top‐down approach is used in this communication to evaluate the role of surface hydrophobicity in bitumen extraction, and to elucidate how molecular interactions alter solid wettability under practical oil sand extraction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In heavy oil extraction, kinetically stable W/O emulsions pose a significant hindrance to bitumen production during the froth treatment process. The bitumen production from oil sands ore involves bitumen extraction from the oil sand ores via hydrotransport, followed by bitumen aeration and flotation, where the resultant froth is on average composed of 60 wt % bitumen, 30 wt % water, and 10 wt % solids . During froth treatment, the majority of water and solids are removed using centrifugation at elevated temperatures (e.g., 80 °C), but up to 3 wt % of water in froth is present in the form of kinetically stable W/O emulsion, which is very difficult to remove.…”
Section: Introductionmentioning
confidence: 99%
“…The bitumen production from oil sands ore involves bitumen extraction from the oil sand ores via hydrotransport, followed by bitumen aeration and flotation, where the resultant froth is on average composed of 60 wt % bitumen, 30 wt % water, and 10 wt % solids. 15 During froth treatment, the majority of water and solids are removed using centrifugation at elevated temperatures (e.g., 80 °C), but up to 3 wt % of water in froth is present in the form of kinetically stable W/O emulsion, which is very difficult to remove. W/O emulsions can be observed throughout the bitumen production process, and some of these processes involve lower operating conditions than froth treatment (e.g., extraction, industrially operated at ∼50 °C).…”
Section: Introductionmentioning
confidence: 99%
“…1 The mixing of two immiscible liquids in the presence of several interfacially active species creates problematic petroleum emulsions which are difficult to break. 2,3,4 Asphaltenes and fine bi-wettable solid particles (clays) are known to stabilize such emulsions since they readily partition at the liquid-liquid interface to create mechanical barriers that resist droplet coalescence. [5][6][7][8][9][10][11][12] Recent research has shown that the continual accumulation of asphaltenes at the oil-water interface leads to the formation of elastically-dominated interfacial layers that rupture once a critical yield stress is exceeded.…”
Section: Introductionmentioning
confidence: 99%